Safe and effective use of a hybrid closed‐loop system from diagnosis in children under 18 months with type 1 diabetes. Issue 1 (5th December 2021) - Tseretopoulou, Xanthippi; Viswanath, Vidya; Hartnell, Sara; Ware, Julia; Thankamony, Ajay; Webb, Emma A.; Hysted, Helen; Ashford, Jennifer; Hendriks, Emile; Teoh, Yun; Williams, Rachel M.
Abstract: The management of type 1 diabetes in infancy presents significant challenges. Hybrid closed loop systems have been shown to be effective in a research setting and are now available for clinical use. There are relatively little reported data regarding their safety and efficacy in a real world clinical setting. We report two cases of very young children diagnosed with type 1 diabetes at ages 18 (Case 1) and 7 months (Case 2), who were commenced on hybrid closed‐loop insulin delivery using the CamAPS FX™ system from diagnosis. At diagnosis, total daily dose (TDD) was 6 and 3.3 units for Case 1 and 2, respectively. Closed loop was started during the inpatient stay and weekly follow up was provided via video call on discharge. Seven months from diagnosis, Case 1 has an HbA1C of 49 mmol/mol, 61% time in range (TIR, 3.9–10 mmol/L) with 2% time in hypoglycemia (<3.9 mmol/L) with no incidents of very low blood glucose (BG; <3 mmol/L, 54 mg/dL) over 6 months. Given the extremely small TDD of insulin in Case 2, we elected to use diluted insulin (insulin aspart injection, NovoLog, Novo Nordisk Inc., Plainsboro, NJ, Diluting Medium for NovoLog®). Six months from diagnosis, the estimated HbA1c is 50 mmol/mol, TIR 76% with 1% hypoglycemia and no incidents of very low BG (<3 mmol/L, 54 mg/dL) over 6 months. We conclude that the use hybrid closed‐loop can be safe and effective from diagnosis in children under 2 years of age with type 1 diabetes.